Goldfinger, Solvent extraction of gold - Johansson, Richard (My University, 2023)
This is a project about the purification of gold at 25 ºC during recycling by solvent extraction. The solvent extraction of gold from chloride media (slightly acidic sodium chloride, choline chloride and a combination of ethylene glycol and choline chloride) by solutions of Aliquat 336 in 3,7-dimethyloctanol was investigated. The 3,7-dimethyloctanol is a semisynthetic diluent which can be obtained by simple chemical processing of a terpene (geranyl acetate) obtained from plants. The behavior of potential impurity metals such as copper, lead, palladium, and zinc, in the solvent extraction purification was assessed. An impure gold solution obtained from scrap gold was successfully purified into a pure gold solution by using a deep eutectic solvent (DES) as the stripping agent made of choline chloride and ethylene glycol at a 1:2 ratio. There is an increasing interest in making solvent extraction more environmentally friendly by using new and green solvents. Deep eutectic solvents (DESs) are a new group of greener solvents that have similar properties as ionic liquids (ILs). The solvent extraction of gold was modelled mathematically, the work included estimations of the random errors. Pitzer and SIT theory was used in the modelling and the parameters for Pitzer and SIT equations were obtained.
Keywords: Gold; Solvent extraction (SX); Leaching; Deep eutectic solvents (DES); Ionic liquids (IL); Distribution ratio (d-value); Activity coefficients